THE INFLUENCE OF MADURESE L1 BACKGROUND ON THE STUDENT’S ENGLISH CONSONANTAL SOUNDS PRODUCTION - Evha Nazalatus Sa'adiyah; Devie Rezti; Luqyana Mufidah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Madura, 2017)
This research is eager to find the English consonantal sounds influenced by Madurese L1 background of students. It employs a qualitative design. The data of the research were recordings of students’ performances during the speaking class collected through observation with snowball technique which followed three phases: description, reduction, and selection, and analysed through three activities: data reduction, data display, and conclusion drawing/ verification. The findings obtained from this research show that tthee were twelve English consonantal sounds that tend to be influenced by students’ first language background. They are the fricatives [v, θ, ð], the voiceless stops [p, t, k], the voiced stops [b, d, g], the alveolar stops [t, d], and the alveolar fricative [s]. The influence caused students to delete or substitute some consonant sounds and also pronounce the aspirated sounds un-aspirated or un-aspirated sounds aspirated. Those difficulties emerged mostly due to the difference in the existence of consonant sounds, the rules of consonant distribution, and the difference in consonant clusters between English and Madurese.